2015
DOI: 10.7860/jcdr/2015/9045.6437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Zygomatic Air Cell Defect using Orthopantomogram

Abstract: INTRODUCTIONPneumatization is the formation of air cavities in bone. Apart from the major paranasal sinuses, air cells may arise singly or in clusters in numerous locations in the skull, including the temporal bone [1]. The nomenclature ZACD is used to denote accessory air cells observed in the zygomatic process of maxilla and articular eminence of the temporal bone, which simulate mastoid air cells [2]. It presents as an asymptomatic, non expansile, non destructive radioluceny on radiographs [3]. Recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…12 Moreover, using panoramic radiography Shokri et al 20 and Khojastepour et al 8 found a frequency of 6.2% (98 cases) and 2.1% (64 cases) respectively in Iran using panoramic radiography. In India, Kishore et al 21 and Patil et al 22 found similar frequencies of 2.5% (63 cases) and 1.82% (141 cases) respectively. Orhan et al 2 reported a similar frequency of 1.88% (19 cases) to the ones reported by Hofmman et al 23 with a frequency of 2.38% (20 cases) and of 1.85% (20 cases) respectively in Germany (Table 4).…”
Section: Discussionmentioning
confidence: 89%
“…12 Moreover, using panoramic radiography Shokri et al 20 and Khojastepour et al 8 found a frequency of 6.2% (98 cases) and 2.1% (64 cases) respectively in Iran using panoramic radiography. In India, Kishore et al 21 and Patil et al 22 found similar frequencies of 2.5% (63 cases) and 1.82% (141 cases) respectively. Orhan et al 2 reported a similar frequency of 1.88% (19 cases) to the ones reported by Hofmman et al 23 with a frequency of 2.38% (20 cases) and of 1.85% (20 cases) respectively in Germany (Table 4).…”
Section: Discussionmentioning
confidence: 89%
“…There is a series of studies which retrospectively evaluated panoramic radiographs, with a determined ZACD prevalence of 1.03% to 3.42% ( 1 , 8 - 14 ). While the subjects of comparative radiology in our study were patients with TMJ disorder, recent studies of ZACD were more based on determining its prevalence by including larger groups of dental patients without previous symptomatology related to the stomatognathic system.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ZACD rarely occurs with additional clinical symptomatology, and it was found accidentally on different radiological images of TMJ area, as described in clinical reports of patients with temporomandibular disorder (TMD) ( 7 ). There are many studies on ZACD prevalence assessed on panoramic radiograph samples ( 8 - 14 ). As in general skeletal radiology, TMJ transcranial diagnosis and multi-slice computed tomography (MSCT) were common tools for evaluation of ZACD, as well as cone beam computed tomography (CBCT) ( 15 - 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Small bony cavities are formed during the pneumatization of normal periosteum. [4] It is a process of asymptomatic expansion of cavities containing air within the bone and temporal bone, ethmoid bone, and mastoid cells are the most important sites of maxillofacial region with infrequent sites including middle ear, squamomastoid, petrous apex, and perilabyrinthine. [5] ZACD appears to be comparable with mastoid air cells and has been represented as accessory air cells which do not cross zygomaticotemporal suture anteriorly and are found to be present within the limitation of zygomatic process and articular eminence of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%